Case Report: Immune Mediated Necrotizing Myopathy With IgG Antibodies to 3-Hydroxy-3-Methylglutaryl-Coenzyme a Reductase (HMGCR) May Present With Acute Systolic Heart Failure - Ghannam, Malik; Manousakis, Georgios (Frontiers in Neurology, 2020)
Involvement of cardiac muscle is felt to be very uncommon in anti-HMGCR myopathy, and therefore early cardiac evaluation is not considered a high priority for this condition. We herein present the case of a 72-year-old woman admitted due to dyspnea and orthopnea, who, in retrospect, suffered from proximal more than distal muscle weakness for 3 months prior to admission. She was found to have acute systolic heart failure. Serologic testing showed positive 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) IgG antibodies, and muscle biopsy showed necrotizing myopathy. No alternative explanation for heart failure was found. Despite immunotherapy and symptomatic treatment, she died from multiorgan failure. Our study suggests that heart failure in anti HMGCR myopathy may not be as rare as previously thought, and therefore early cardiac evaluation should be considered in patients with this diagnosis, to minimize morbidity and mortality.